2006
DOI: 10.1111/j.1574-695x.2006.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic culture conditions favor biofilm-like phenotypes inPseudomonas aeruginosaisolates from patients with cystic fibrosis

Abstract: Pseudomonas aeruginosa causes chronic infections in the lungs of cystic fibrosis (CF) individuals and remains the leading cause of morbidity and mortality associated with the disease. Biofilm growth and phenotypic diversification are factors thought to contribute to this organism's persistence. Most studies have focused on laboratory isolates such as strain PAO1, and there are relatively few reports characterizing the properties of CF strains, especially under decreased oxygen conditions such as occur in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 32 publications
8
51
1
Order By: Relevance
“…Of note, it was clearly demonstrated that the oxygen potential was decreased inside this thick mucous layer (56). Importantly, the results of previous studies by our group and others have revealed that P. aeruginosa, when grown by anaerobic respiration, forms robust biofilms (29,57,60). These data further implicate the clinical relevance of the biofilm mode of bacterial growth inside the mucous airway of CF patients.…”
supporting
confidence: 69%
“…Of note, it was clearly demonstrated that the oxygen potential was decreased inside this thick mucous layer (56). Importantly, the results of previous studies by our group and others have revealed that P. aeruginosa, when grown by anaerobic respiration, forms robust biofilms (29,57,60). These data further implicate the clinical relevance of the biofilm mode of bacterial growth inside the mucous airway of CF patients.…”
supporting
confidence: 69%
“…Thus, it seems likely that the biofilm defect in this strain was multi-factorial, given the large number of genes differentially regulated in the phoQ mutant. As P. aeruginosa growth in the cystic fibrosis lung has been proposed to be biofilm-like (Garcia-Medina et al, 2005;O'May et al, 2006) this PhoQ-dependent adaptation may help protect the bacteria from the host. If true, this may explain why the phoQ mutant, deficient in biofilm formation, was deficient in survival in the rat lung.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been recently reported that biofilm produced by strains of P. aeruginosa and B. cenocepacia is favoured by environmental stimuli, including oxygen deficiency and iron availability (3,18). With regard to iron, the concentration of iron and Lf in damaged CF respiratory tissues is high if compared to that of healthy controls (4)(5)19).…”
Section: Discussionmentioning
confidence: 99%